The influence of education and income on the psychopathological profile of post-bariatric patients - Vieira, Nélio Barreto (Revista JRG de Estudos Acadêmicos, 2025)
Introduction: Bariatric surgery is an effective intervention for controlling severe obesity, but psychosocial factors such as education and income can significantly influence postoperative outcomes, especially with regard to mental health. Objective: To analyze the influence of education and income on the psychopathological profile of patients undergoing bariatric surgery. Methods: Cross-sectional study, with convenience sampling, involving 124 bariatric patients monitored by a multidisciplinary team. Validated instruments were used to assess symptoms of stress, anxiety, depression, binge eating, and personality traits. Data collection was performed using an online questionnaire and the data were analyzed with statistical tests appropriate to the nature of the variables, adopting a significance level of 5%. Results: It was found that patients with lower education and income had significantly higher scores on dysfunctional psychological and behavioral symptoms. The presence of binge eating and traits of emotional isolation was more prevalent among individuals in situations of social vulnerability. Conclusion: The results point to the importance of considering the social determinants of health in the monitoring of post-bariatric patients. Psychosocial interventions should be incorporated systematically, with special attention to educational and economic inequalities, promoting comprehensive and equitable care.